Pengaruh Current Ratio, Debt to Equity Ratio, dan Return on Assets terhadap Nilai Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di BEI Periode 2022-2025 - Fatima Zahara; Istianingsih Sastrodiharjo; Aloysius Harry Mukti (International Forum of Researchers and Lecturers, 2026)
This study aims to examine and analyze the influence of the Current Ratio, Debt to Equity Ratio, and Return on Assets on Firm Value in Consumer Non-Cyclical Companies listed on the Indonesia Stock Exchange for the 2022-2025 period. This research method uses a quantitative approach with secondary data sources obtained from the companies' financial reports. The sampling technique used was purposive sampling, resulting in 156 processed data samples that met the criteria. The analysis method used is descriptive statistical analysis test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), correlation test, multiple linear regression analysis test, and hypothesis test (significance test F test, t test, and coefficient of determination test R2 with SPSS 27 statistical tools. The results of this study indicate that: 1) Current Ratio has a negative effect on company value, 2) Debt To Equity Ratio has a negative effect on company value, 3) Return On Assets has a negative effect on company value.